Evaluation of the thermal integral as an environmental factor for thecultivation of hydroponic lettuce in the floating rootsystem in the town of Lima - Chuquicondor Villafuerte, Rafael (2024)
The hydroponic system is a closed and efficient systemfrom the economic, technical and environmental point of view, considerably reducing stress, fertility and soil depletion, improving food quality and therefore the quality of life of Peruvians. The study was conducted atthe Experimental Center (INVERGEP SAC), locatedin the Boza community in Huaral, Lima, Peru. The objective was to produce lettuce (Lactuca sativa) using the hydroponicsystem, applying techniques of the NFT model, and to promote newalternatives to generate intermediate technology production chainssuch as hydroponic crops for rural and urban communities. Using athermohygrometer, the phenological process was carried out in thehatching stage and in the harvesting stage, obtaining the thermalsummation. Data were obtained from the daily register in referencevalues of the experimental module to evaluate in the hatching coverand then in the harvest phase: first in the seedling stage GDD = 11.2º C; GDA = 71. 8º C, during the vegetative period; GDD = 11.2°C;GDA = 289.76 C . The research work was carried out during onemonth and a half; from September 1 to October 6, 2023. The dailyaccumulated temperature index, during the whole vegetative period,shows that the sector of the northern Lima locality is suitable forthe installation of hydroponic cultivation because it has minimumtemperatures from 11°C to 19°C.